The Causal Relationship Between Spa Experience Management, Spa Service Quality, Customer Satisfaction, and Customer Loyalty Toward Day Spas in Bangkok - Puangniyom, Piyachat; Choibamroong, Therdchai (Business Administration and Management Journal Review, 2021)
Spa industry is part of wellness tourism. Thailand is seen as a spa destination among tourists. It can be seen from the growing value of the Thai spa industry. This research was aimed at examining direct and indirect effects of the causal relationships between spa experience management, spa service quality, customer satisfaction, and customer loyalty in the context of day spas established in Bangkok. Quantitative method research was adopted. Questionnaire was developed to serve as a research instrument to collect the required data from 400 Thai respondents who had received spa services from day spas in Bangkok. Purposive sampling was a technique of questionnaire distribution. Descriptive statistics and structural equation modelling were used to analyze the data and information. The results revealed that spa experience management had direct effects on customer satisfaction and customer loyalty. Meanwhile, spa service quality exerted direct effects on customer satisfaction but not directly influencing customer loyalty. Besides, it was found that customer satisfaction played a mediating role in the relationships between spa experience management and customer loyalty and between spa service quality and customer loyalty.